Recent Academic Contributions to the study of Tango (Revista Argentina de Musicología, 2015)
Tango studies can cover a wide thematic range. The three main issues are music, literature and dance, and around each of them the number of topics that can be developed is huge. But while much is published about tango, academic production is limited. In this paper I present some of the works on tango that are being made from musicology, and academic studies about the genre made from other disciplines. I do not pretend to be exhaustive, but to point out some interesting and productive approaches. I will refer to works that are addressed from the perspective of cultural heritage and industry which unfolds around tango, studies on tango lyrics, essays addressing the genre from various angles, studies inspired by his reterritorialization, several aspects related to dance, and others related to its history and political history.
Keywords: tango; tango lyrics; danced tango; tango bibliography